Re-enacting Space: Behind and in front of the Lidar Camera (Architecture Image Studies, 2025)
This article investigates how scanning can be appropriated as part of practice-based research probing notions of body extension. It is a practice I developed alongside writing the artist’s book ‘Tupaia, Kybernetes & Lara Croft’, a monograph that could be seen as the so-called B-sides of my PhD - the book gathers ideas that did not make it into the final PhD version.  Author Biography                                                 Eva Sommeregger, Senior Scientist, Academy of Fine Arts, Vienna ; Senior Researcher, Art Academy of Latvia, RigaDr. Eva Sommeregger is a registered architect, researcher and educator based in Vienna. She is co-founder of eyeTry architecture, Senior Scientist at the Academy of Fine Arts Vienna and Senior Researcher at the LMDA. Eva received Masters Degrees from the Bartlett UCL London and the TU Vienna and a PhD from the Academy of Fine Arts Vienna. She was Schütte-Lihotzky Research Fellow 2010 and Architect in Residence at the MAK in Los Angeles 2011. In 2018, she co-founded the Magazin exhibition space for contemporary architecture in Vienna. Her research deals with models of thought related to the human body’s spatiality, her practice involves writing, curating and developing experimental digital spaces that have been exhibited at venues such as the MoMa New York City and the Venice Biennale of Architecture.